It Is Time, It Is Past Time, To Resolve The Abortion Debate - Block, Walter E. (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
Debates over bodily autonomy and abortion often polarize between pro-choice and pro-life positions. “Evictionism” offers a third perspective, framing pregnancy through the lens of property rights and bodily sovereignty: a woman has full ownership of her body, and a fetus is considered an innocent but unauthorized occupant. This study explores evictionism within a critical realist paradigm, recognizing the layered reality of biological processes, social structures, and technological possibilities. It situates the argument in socio-economic contexts where access to reproductive healthcare, legal frameworks, and medical technology shape women’s autonomy and fetal viability. Using a critical realist approach, this research employs theoretical analysis and socio-economic contextualization. The study identifies ontological layers of pregnancy (biological, legal, and cultural), explores causal mechanisms (property rights discourse, medical technologies enabling fetal survival, and social norms), and evaluates agency-structure interactions. Data are drawn from legal texts, bioethical literature, and socio-economic reports on reproductive healthcare access. The methodology emphasizes retroduction to uncover underlying mechanisms and assesses how technology and policy mediate ethical positions on evictionism. Findings indicate that evictionism functions as a contingent ethical framework, deeply dependent on material conditions. In socio-economic settings with advanced neonatal care, evictionism converges with pro-life outcomes in late-term pregnancies while maintaining bodily autonomy. In contexts with limited healthcare infrastructure, evictionism’s overlap with pro-choice outcomes becomes pronounced due to technological constraints. The analysis reveals that bodily autonomy cannot be abstracted from socio-economic realities and power structures. Critical realism highlights evictionism’s emancipatory potential while cautioning against reducing bodily integrity to property metaphors without addressing systemic inequalities.